An Epidemiological Study Of Genital Tract Infection Among Infertile Women (International Journal of Food and Nutritional Sciences, 2022)
Background: The goal of this study was to identify the profile of genital tract infections and their relationship with clinical and demographic parameters as well as tubal diseases among infertile women in Ghaziabad.Aim and Objective: To study of genital tract infection among infertile womenMethodology: It was a hospital-based prospective observational study that involved all couples visiting the Obstetrics and Gynecology department's out-patient clinic at Santosh Medical College and Hospital, Ghaziabad. An 18-month period, from January 2019 to June 2020, was used for the study's execution. 172 couples who met the inclusion criteria were enrolled in the study out of a total of 193 couples who were recruited and investigated. However, 10 patients' investigations weren't completed for 10 patients, and 11 couples were lost to follow-up.Result: Only 8 male partners (4.6%) displayed signs of a genital tract infection. 5 of them were in the group with primary infertility. Between the two groups, the results were not comparable.Conclusion: A marked proportion of infertile women have genital tract infections that can significantly influence their reproductive function and performance. These infections should be routinely screened and treated properly to prevent their consequences, such as infertility, which is especially important in developing countries.